PENGARUH PERENCANAAN PAJAK, STRUKTUR MODAL DAN BIAYA OPERASIONAL TERHADAP PENGENAAN PAJAK PENGHASILAN BADAN - Nurfadillah, Sadriyah; Zenabia, Tsarina (Jurnal Nusa Akuntansi, 2024)
This research aims to find out and provide empirical evidence regarding tax planning, capital structure and operational costs regarding the imposition of corporate income tax in Consumer Non-Challical companies in the food and beverage sub-sector listed on the Indonesia Stock Exchange for the 2018-2022 period. The type of research used is quantitative research. The number of samples in this study was 90 observation data from 18 Consumer Non-Challical companies in the food and beverage sub-sector for the period 2018-2022 which was obtained using a purposive sampling method based on the criteria that had been carried out. The data used is secondary data, namely in the form of audited financial reports for 2018-2022 obtained from the official website of the Indonesian Stock Exchange and the official websites of each company. The data analysis technique used is multiple linear regression analysis using e-views 12 software. The results of this research based on partial test results state that tax planning, capital structure and operational costs influence the imposition of corporate income tax. Based on the simultaneous test, it is stated that tax planning, capital structure and operational costs simultaneously influence the imposition of corporate income tax.